Pengaruh Penambahan Arang Tempurung Kelapa Terhadap Kualitas Briket dari Arang Pelepah Nipah Menggunakan Tepung Tapioka Sebagai Perekat - Mohamad Arifin; Rosita Dwityaningsih; Taufan Ratri Harjanto (P3M Politeknik Negeri Cilacap, 2023)
Nipa Palm fronds is one of the biomass that has potential to be used as briquettes because it has high cellulose. The calorific value of nypa palm frond will cause low briquettes quality. The aims of this study is to determine the effect of the addition of coconut shell charcoal. The research method used was by mixing coconut shell charcoal with nipa palm charcoal with various compositions and using tapioca flour as an adhesive as much as 10% of the total weight of briquettes. It was found that the addition of coconut shell charcoal can improve the quality of briquettes according to SNI No.1/6235/2000 with the best composition ratio palm charcoal:coconut shell charcoal which is 20%:80%. Briquettes have a moisture content 2,43%, ash content 7,3%, a calorific value 6779,64 Kal/gram, density 1 gram/cm2 and a burning rate of 0,0393 gram/minute.